Effect of sowing time on the grain yield and fodder potential of sorghum undersown with stylo in the subhumid zone of Nigeria - Mohamed-Saleem, M.A. (1985)
Undersowing sorghum with stylo as a means of improving fodder quality for dry-season grazing of livestock in the subhumid zone of Nigeria was investigated. Planting either Stylosanthes guianeusis cv 'Cook' or S. hamata cv 'Verano' simultaneously with local or improved varieties of sorghum reduced grain yield by over 70%, but the loss was overcome or minimized by delayed planting of the stylo by 3-6 weeks. Improvement in quality of the resulting fodder from fodder from stylo planted between weeks three and six after the sorghum crop made up or even increased the total value of production per area of land. Stylo yield was very much reduced if planted six weeks later than the cereal croUndersowing at the appropriate time is considered to be a way of improving the quality of crop residues in an agro-pastoral community without extra demands on labour.